Catechol-Bearing Polymeric Nanoparticles for Antioxidant Therapy. Issue 1797 (21st May 2015) - Hasegawa, Urara; Moriyama, Masaki; Uyama, Hiroshi; van der Vlies, André J.; Metzger, Stéphanie; Ehrbar, Martin
ABSTRACT: Polymeric nanoparticles having redox-active catechol moieties, a common structural motif found in naturally-occurring antioxidants, were developed. We synthesized an amphiphilic catechol-bearing polymer that self-assembled to form nanoparticles with a diameter of 126 nm. The nanoparticles showed enhanced ROS-scavenging activity compared to the small catecholic compound dopamine. Furthermore, the nanoparticles inhibited ROS-mediated angiogenesis as shown by the endothelial cell tube formation assay and the chicken chorioallantoic membrane (CAM) assay.